PENGGUNAAN LKS KOMIK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 9 PEKANBARU - Hari Bowo; Herdini '; Erviyenni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aims to increase student learning achievement on the topic of hidrocarbon in class X Senior High School (SMAN) 9 Pekanbaru. LKS comic dressed student is able to stimulate the brain while reading it, because it displays images that are not boring for students. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class X5 as the experimental class and students of class X6 as the control class. Experimental class is a class that is applied to comic worksheet while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount> ttable is 2.75>1.66, means that worksheet use of comics can improve student learning achievement on the topic of hidrocarbon in class X Senior High School (SMAN) 9 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,73. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,62.Keywords : Learning Achievement, LKS Comic, and Hidrocarbon